[Behind rebel lines ; Tullahan River ; Aizamania] - Lazaro, Cheche (Quezon City Probe Productions, 1988)
Features the ceasefire between NPA rebels and the military with the interview of TPT with the insurgents ; a polluted river and its damage to environment and interview with Aiza Seguerra.
Behind rebel lines (23 min.) -- Tullahan River (12 min.) -- Aizamania (11 min.)
VHS.
Keywords: Seguerra, Aiza; Terrorism -- Philippines -- Quezon Province; Rivers -- Philippines; Tullahan River